Taxpayer awareness: a bibliometric vosviewer analysis from harzing’s publish or perish - Sanjaya, Nathasya Febrista (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to analyze research literature on taxpayer awareness using bibliometric analysis using VOSViewer and Harzing's Publish or Perish software. This research found that Taxpayer Awareness is a topic that has been widely researched in recent years. This research looked at scientific publications using the keyword "Taxpayer Awareness" over a period of 10 years, namely from 2014 to 2024 with the results of 500 scientific journals which were then filtered to become 449 scientific journals. Mapping results using VOSViewer show a strong relationship between taxpayer awareness and taxpayer compliance. The literature review study also confirms that taxpayer awareness has a positive influence on taxpayer compliance in paying their tax obligations. So it can be interpreted that the higher the awareness of taxpayers, the more compliance in paying taxes will also increase. Suggestions for further research are to link research between keywords Taxpayer Awareness with Tax Evasion, Tax Morale, and Service Tax, because in the network visualization map there is no line that connects these things and there is an opportunity for further research in the future.